Nexus Water-Energy-Food Approach as Decision-Making Support for Climate Resilience: A Case Study in the Mogi Guaçu River Basin - Pestana, Laura de Oliveira Battistini; Olmedo, Jacqueline Priscila; Silva, Keila Camila da; Ventura, Katia Sakihama (National Journal of City Management, 2025)
Objective – To analyze water, energy, and food security through the Nexus approach as a decision-making support tool aimed at enhancing climate resilience in the Mogi Guaçu River Basin. Methodology – Deductive research based on qualitative data published on the Brazilian government platform AdaptaBrasil MCTI. The study was conducted in three stages: data collection; analysis of information through georeferenced maps; and the proposal of adaptation measures based on the Nexus approach. Originality/relevance – The study integrates water, food, and energy security within the context of climate change, particularly in river basins. By highlighting mitigation measures with intersectoral impacts, it connects governance and regional planning themes. Results – The water sector was identified as the most threatened during drought periods. The proposed measures emphasize actions to foster climate education, improve water governance, and seek alternatives for agricultural production. Theoretical/methodological contributions – The adoption of the Nexus approach as a tool for integrated analysis and decision-making support. Methodological contribution using data made available on a public consultation platform for territorial diagnosis. Social and environmental contributions – The study proposes measures to strengthen cooperation between the analyzed sectors and to support climate resilience in river basins. It emphasizes the importance of integrated planning for environmental security and quality of life.